The sustainable enterprise profiting from best practice - Brown, Christopher Stephen (Gale virtual reference library, 2005)
Aims to assist those running or advising organizations of all types and sizes in understanding the business case for sustainable development and corporate social responsibility. Tackles the subject from many different perspectives; offering advice and guidance in preparing and implementing programs and policies appropriate for the different contexts in which businesses operate.